2013
DOI: 10.1002/srin.201300293
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cold Rolling on Microstructural Evolution in 2205 Duplex Stainless Steel

Abstract: The influence of cold rolling on the microstructural changes of 2205 duplex stainless steel was investigated. The steel samples revealed the presence of almost equal volume fraction of δ‐ferrite and austenite phase after hot rolling. During cold rolling, the above phase constituents became flattened, fragmented as well as transformed into acicular microstructural constituents with increasing amount of cold deformation. The transmission electron microscopy revealed the presence of strain‐induced α′ martensite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 38 publications
4
42
0
1
Order By: Relevance
“…Substantial references have been published focusing on the mechanisms of cold work/pre-straining on the LCF behaviours of ASS, aluminium and magnesium alloy [13][14][15][16][17], among which CL Zhou et al [18,19] investigate the effects of prior tensile plastic deformation on the torsional fatigue properties of a structural steel. As for the DSS, however, the researchers are mainly concerned with the effects of pre-straining/cold-work on the basic mechanical properties, microstructural evolution during monotonic loadings [20][21][22][23][24]. Much more efforts should be made to explore how it works on the subsequent LCF behaviours and reveals the corresponding mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial references have been published focusing on the mechanisms of cold work/pre-straining on the LCF behaviours of ASS, aluminium and magnesium alloy [13][14][15][16][17], among which CL Zhou et al [18,19] investigate the effects of prior tensile plastic deformation on the torsional fatigue properties of a structural steel. As for the DSS, however, the researchers are mainly concerned with the effects of pre-straining/cold-work on the basic mechanical properties, microstructural evolution during monotonic loadings [20][21][22][23][24]. Much more efforts should be made to explore how it works on the subsequent LCF behaviours and reveals the corresponding mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Between 550 and 9508C, the ferrite phase will principally transform into the sigma phase and secondary austenite. [1,2,5] The chi phase may also form in the sigma-phase formation temperature range, but it is usually secondary to the sigma phase in quantity. [7] In both of the temperature regimes mentioned, carbides may also form.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The ferrite phase is almost always considered the unstable phase, whereas the austenite phase is thought to undergo nearly no changes at all. [1][2][3][4][5] Below 5508C, two new ferrite phases may form from the original ferrite. The two new ferrite phases are respectively enriched with Cr and Fe, and they may form through spinodal decomposition or the nucleation-and-growth mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the effect of martensitic transformation on the strength and ductility of stainless steels subjected to cold plastic deformation under temperatures in the M s -M d interval of metastability, continued to be investigated [12][13][14][15][16][17][18][19][20][21] . Gauss et al 12 found 78% of γ martensite after 39% of plastic strain in AISI 201 steel.…”
Section: Introductionmentioning
confidence: 99%
“…Gauss et al 12 found 78% of γ martensite after 39% of plastic strain in AISI 201 steel. Pramanik et al 13 revealed the presence of strain-induced martensite during cold rolling of a duplex stainless steel. Hamada et al 14 indicated that in 201 and 201L steels strain-induced martensite is the dominant mechanism controlling the tensile flow and work hardening rate at temperature from -80 °C up to room temperature.…”
Section: Introductionmentioning
confidence: 99%